Effect of Water Deficit on Growth and Leaf Gas Exchange of Pepper Plants (Capsicum Annuum L) - Awad, Mohamed Hamad (2001)
The effect of different treatments of soil moisture on leaf gas exchange, growth and several metabolic parameters was investigated in three cuItivars of chilli pepper plants Capsicum annuum L. The study was done in potted plants under protective environment agriculture. The alteration in tissue water relations of leaves at different water deficit regimes was studied by pressure chamber techniques. Results revealed that the rate of photosynthesis decreased as leaf water status declined, and was more closely related to leaf water potential. Leaf conductance and , net photosynthesis were significantly correlated to leaf water potential in severe water deficit. The close relationship between leaf conductance and net photosynthesis found at different level of water deficit showed that stomatal regulation effectively controlled the water balance (low transpiration rates) of the leaf at the expense of lower rate of photosynthesis. Re-watering stressed plants brings all leaf gas exchange parameters near to that of control plants. Stomatal conductance of chili pepper plants is more sensitive to soil drying and start to close before any appreciable reduction in leaf water potential, suggesting that there is signal coming from the root system trigger stomatal closure. Exposure to soil drying progressively reduce leaf soluble protein content and increase the level of accumulated proline. Measuring peroxidase activity level and xylem sap pH revealed that both parameters increase during soil drying and leaf expansion rates fall. This suggests that there is a role for both parameters in controlling leaf expansion rate. In another experiment, plants were subjected to partial root drying and the roots in contact with the drying soil were removed. The results revealed that leaf gas exchange parameters and leaf elongation rates declined, the removal of roots in contact with drying soil trigger the increment of leaf gas exchange parameters and leaf growth rates. This suggests that there is a positive signal coming from the root system controlling shoot processes which could be used in agriculture to minimize plants water requirements and to regulate growth.